Metabolomic Analysis of Diet-Induced Obese Mice Supplemented with Eicosapentaenoic Acid - Nishitani, Shigeki; Fukuhara, Atsunori; Jinno, Yasutaka; Kawano, Hiroyuki; Yano, Takashi; Otsuki, Michio; Shimomura, Iichiro (Experimental and Clinical Endocrinology & Diabetes, 2018)
Eicosapentaenoic acid (EPA) is an omega-3 fatty acid with anti-inflammatory effects. To determine the effects of EPA on metabolic pathways in obese adipose tissues and liver, mice were fed normal chow diet (NCD), high-fat diet (HFD), or 3% EPA-containing high fat diet (HFD+EPA) for 8 weeks. Metabolomic analysis was performed using epididymal adipose tissues (epi WAT) and liver. Metabolites that were specifically elevated in HFD+EPA, were assessed for their anti-inflammatory properties using RAW264.7 macrophage cells. Body and adipose tissue weights were significantly higher in HFD than NCD, and lower in HFD+EPA than HFD. Plasma insulin levels were significantly higher in HFD than NCD, and lower in HFD+EPA compared with HFD. Plasma monocyte chemotactic protein-1 (MCP-1) levels were higher in HFD than NCD, and tended to be lower in HFD+EPA than HFD. The levels of intermediate metabolites in the glycolytic pathways were lower in HFD compared with NCD and HFD+EPA in both epi WAT and liver, while intermediate metabolites of the TCA cycles were elevated in HFD and HFD+EPA compared with NCD in epi WAT. Among the metabolites in epi WAT, the levels of thiaproline, phenaceturic acid, and pipecolic acid were specifically elevated in HFD+EPA, but not in HFD or NCD. Treatment of RAW264.7 cells with thiaproline significantly ameliorated LPS-induced iNOS expression, while pipecolic acid inhibited LPS-induced IL-1β expression. These results suggest that EPA normalizes glycolytic pathway intermediates in both epi WAT and liver, and induces metabolites with anti-inflammatory properties.
Keywords: eicosapentaenoic acid; adipose tissue; obesity; inflammation